Development of a technical advisory service for managers of sewage treatment plants - Suki, Anhar; H., Jenny; Nosree, P.; Palaux, B. (1988)
It has been noticed the need to develop a Technical Advisory Service (TAS) for the managers of sewage treatment plants (STP) in Malaysia. This involves technical visits to the STP on regular basis to check its running condition and to provide management advice on the operation and maintenance of the plant. The objectives of the TAS is to upgrade the management practice in the local STP to improve the eeficiency of the STP to centralise the relevant data and to improve the technological know-how of the professionals in the field of wastewater treatment. The TAS is modelled on the French experience with modification to suit the local condition. The proposed TAS software and an IBM PC/AT computer. The database structure with the various file categorisation is presented together with the possible network structure. Initial discussions on the administrative structure and the financial aspect is also included.